Papel da obesidade e imunossenescência precoce na COVID-19 - Madruga, Mailton Prestes (2022)
The disease caused by the zoonotic virus SARS-COV-2, COVID-19, has high infectivity and low lethality among younger individuals without comorbidities. However, among elderly and individuals with comorbidities (including obesity) it leads to severe acute respiratory syndrome (SARS) and high mortality. This disease is characterized by a large secretion of pro-inflammatory mediators in the lung and other tissues in a systemic way, excess of young neutrophils (emergency myelopoiesis), and activation of the inflammasome complex. In addition, there is lymphopenia and a predominance of activated, exhausted and cytotoxic T cells, especially associated with progression to severe COVID-19. Similarly, in aging and obesity, there is an increase in low-grade basal inflammation, called “inflammaging”, associated with the development of multi-morbidities and death. Breakdown of the intestinal barrier is often related to obesity and may contribute to systemic inflammation, lymphopenia, and worsening of the clinical picture in COVID-19. However, it is largely unknown the influence of obesity, as a model of premature aging, in the immunopathology of COVID-19. Thus, the objectives of this dissertation were to investigate whether obesity in severe COVID-19 was associated with: (a) early immunosenescence, (b) dysregulation of adaptive immunity (especially T lymphocytes) and (c) Microbial Translocation. Fifty in patients with severe COVID-19 were recruited and divided into two groups: 22 non-obese and 28 obese. Eleven COVID-19 negative controls were recruited. Immediately after admission, blood samples were collected, and peripheral blood mononuclear cells (PBMCs) were isolated by density gradient. PBMCs were immunophenotyped to investigate the frequency of monocyte subtypes, B, NK and T cells in relation to their functional stages (activation and exhaustion) and development (including the senescent cells CD27-CD28-). Overall, obese patients showed earlier activation of CD8+ T lymphocytes and lower frequency of effector memory CD4+ cells compared to non-obese patients with COVID-19. The intermediate developmental stage of T lymphocytes was found higher in obese than in non-obese. Overall, obese patients showed delayed activation of CD8+ T lymphocytes (HLA-DR+CD38+GZB) compared to non-obese patients with COVID-19. The intermediate developmental stage of T lymphocytes (CD8+CD27-CD28+CD57+CD45RA+) was higher in obese than in non-obese. There was one microbial translocation in both groups of patients when compared to the uninfected control group. Therefore, obese patients show lower T lymphocyte activation in parallel with microbial translocation, possibly contributing to the process of immune system dysregulation. However, early immunosenescence was not evidenced in obese subjects with moderate COVID-19.